Environmental crimes and green criminology in Bangladesh - Sharif, Sherajul Mustajib (Criminology & criminal justice, 2023)
Bangladesh is an environmentally vulnerable country, where environmental crimes are massive and common. However, the environmental crime prevention mechanism in the country is very weak, and traditional policing is utilized to stop these crimes. Therefore, the green criminological approach to prevent environmental crimes in Bangladesh is underdeveloped in many ways, with a total absence of the green policing model. Hence, this study focuses on attaining a critical understanding of environmental crimes in Bangladesh by exploring the key underlying factors of environmental crimes. It also attempts to contribute to the environmental crime prevention mechanism by recommending a green policing model, while identifying the key weaknesses of the existing environmental crime prevention approach. This article implements the qualitative technique of data collection, and the analysis is based on an in-depth interview of 25 respondents, belonging to different categories of stakeholders, and participant observation. It also analyses the content of newspapers to understand the patterns of environmental crimes in Bangladesh. This article finds that environmental crimes are propagated by several political, economic, institutional, and social elements, such as the political affiliation of criminals, economic profit from natural resources, absence of institutional collaboration, and lack of social consciousness. The issue has become further aggravated due to the weakness of the crime prevention mechanism. Thus, the findings of this study suggest that environmental crimes in Bangladesh should be considered and understood from green criminological perspectives and the development of a green policing model would be effective in reducing environmental crimes in the country.